CatSper mediates not only chemotactic behavior but also the motility of ascidian sperm - Kijima, Taiga; Kurokawa, Daisuke; Sasakura, Yasunori; Ogasawara, Michio; Aratake, Satoe; Yoshida, Kaoru; Yoshida, Manabu (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Sperm motility, including chemotactic behavior, is regulated by changes in the intracellular Ca2+ concentration, and the sperm-specific Ca2+ channel CatSper has been shown to play an important role in the regulation of intracellular Ca2+. In particular, in mammals, CatSper is the only functional Ca2+ channel in the sperm, and mice deficient in the genes comprising the pore region of the Ca2+ channel are infertile due to the inhibition of sperm hyperactivation. CatSper is also thought to be involved in sea urchin chemotaxis. In contrast, in ascidian Ciona intestinalis, SAAF, a sperm attractant, interacts with Ca2+/ATPase, a Ca2+ pump. Although the existence of CatSper genes has been reported, it is not clear whether CatSper is a functional Ca2+ channel in sperm. Results: We showed that CatSper is present in the sperm flagella of C. intestinalis as in mammalian species, although a small level of gene expression was found in other tissues. The spermatozoa of CatSper3 KO animals were significantly less motile, and some motile sperms did not show any chemotactic behavior. These results suggest that CatSper plays an important role in ascidians and mammals, and is involved in spermatogenesis and basic motility mechanisms.